Ventusium: a place of wind - van Sittert, Sybrand (University of the Free State, 2022)
Th is book concerns itself with the infl uence that substance has on architecture and architectural engagement. Architectural substance is explored through the register of the imagination, a term coined by James K.A. Smith to refer to human’s everyday understanding of the world. Th e register of the imagination is informed via the senses through substance, so the senses and their interaction with the world form a large part of the practical discourse of this document. Th e senses lead to practical ways in which to create architecture which includes the entire body and leads to meaningful engagement with the world, and the creation of meaning through the mythology of the building.
Dissertation(M.Arch. (Architecture))--University of the Free State, 2022
Keywords: Imagination; Fabric; Substance; Landscape; Colporteur; Motherhood; Detailing; Experience; Mythology; Mystic; Edge condition